2015
DOI: 10.3171/2014.10.spine14186
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as an independent predictor of reoperation after lumbar laminectomy: a study of 500 cases

Abstract: OBJECT This study aimed to identify the factors predicting an increased risk for reoperation in patients who had undergone a lumbar laminectomy. METHODS The authors retrospectively reviewed the electronic medical records of all patients who had undergone firsttime, bilateral laminectomy at 1, 2, or 3 levels for lumbar spondylosis at the authors' institution. Patients who underwent fusion, laminotomy, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 19 publications
3
15
1
1
Order By: Relevance
“…Smokers are known to have higher reoperation rates after lumbar laminectomy 58 and lower fusion rates after lumbar fusion. 59 , 60 In our study, they exhibited somewhat smaller improvements in SIJ pain and ODI, but these differences were not statistically significant. Although smoking may impair bone growth onto titanium implants, 61 , 62 the effect appeared to be minor.…”
Section: Discussioncontrasting
confidence: 65%
“…Smokers are known to have higher reoperation rates after lumbar laminectomy 58 and lower fusion rates after lumbar fusion. 59 , 60 In our study, they exhibited somewhat smaller improvements in SIJ pain and ODI, but these differences were not statistically significant. Although smoking may impair bone growth onto titanium implants, 61 , 62 the effect appeared to be minor.…”
Section: Discussioncontrasting
confidence: 65%
“…4 A separate study demonstrated higher rates of reoperation among smokers receiving a single-or multiple-level laminectomy. 6 Similar results have also been noted for minimally invasive spine surgery. Gulati et al reported decreased improvement in patient Oswestry Disability Index (ODI) scores at 1 year among smokers relative to nonsmokers following microdecompression for lumbar spinal stenosis.…”
supporting
confidence: 75%
“…This smoking-related disk degeneration provides a likely explanation for the higher rates of recurrent or adjacent-level disease requiring reoperation observed in numerous studies. 31 32 33 34 35 Nicotine is also a central pain-modulating agent and individuals with higher rates and intensity of spine-related pain may be predisposed to addiction to help mitigate their symptoms. 6 36 37 38 Finally, the higher incidence of depression among smokers predisposes this population to increased back-related disability, which could negatively affect postoperative outcome measures.…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%